2019
DOI: 10.1111/fwb.13373
|View full text |Cite
|
Sign up to set email alerts
|

Parallels and contrasts between intermittently freezing and drying streams: From individual adaptations to biodiversity variation

Abstract: Intermittently freezing and drying lotic systems are common in many parts of the world. These ecosystems provide dynamic habitats for biota, as both freezing and drying processes result in the loss of water flow along stream and river channels. However, research into the ecological effects of intermittent freezing on stream biota has remained relatively scarce compared to the recent increase in studies exploring the ecology of intermittent streams that dry. Climate change is predicted to alter the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 110 publications
(205 reference statements)
0
28
0
Order By: Relevance
“…small size) which evolved within a species’ lineage in response to other selective pressures may also confer an advantage against drought. For example, some of the same mechanisms that protect benthic invertebrates from desiccation in intermittent streams may also be beneficial in systems that periodically freeze (Tolonen et al., 2019). Boreal invertebrate communities may thus already possess some traits that could enable persistence despite drying.…”
Section: Discussionmentioning
confidence: 99%
“…small size) which evolved within a species’ lineage in response to other selective pressures may also confer an advantage against drought. For example, some of the same mechanisms that protect benthic invertebrates from desiccation in intermittent streams may also be beneficial in systems that periodically freeze (Tolonen et al., 2019). Boreal invertebrate communities may thus already possess some traits that could enable persistence despite drying.…”
Section: Discussionmentioning
confidence: 99%
“…Under this scenario, Mediterranean freshwater ecosystems are expected to face a huge species loss (Chiu et al, 2017), due to the harsh environmental conditions induced by both hydrological alterations and habitat fragmentation, which act as a filter and select for species displaying specific traits that enhance their survival in these extreme environments (Datry et al, 2017c). In particular, drying up of the streambed causes longitudinal, lateral and vertical habitat fragmentation, limiting the recruitment of new individuals, which drift from upstream or colonizing the riverbed from lateral refugia, such as pools, or from the hyporheic zone, with consequences on species distribution and abundances (Tolonen et al, 2019). Focusing on diatom communities, it has been recently demonstrated that droughts in Mediterranean streams can led to a significant decrease of endangered species (Falasco et al, 2016a), thus reducing species diversity at both local and regional scale, and to changes in community functional traits (Elias et al, 2014;B-Béres, et al, 2019;Novais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Flow intermittency also changes diatom community composition throughout the year, with shifts from lotic-to lentic-adapted species up to aerophilous ones during the lentification and the drying up of the riverbed respectively (Datry et al, 2017a). Thus, species surviving during the lentification phase can often represent both a taxonomic and functional subset of those typical of the wet phase (Tolonen et al, 2019). In addition, modifications in river physical elements (such as river banks, channel morphology, substrate composition and riparian canopy) induced by land use changes can play an important role as drivers of diatom composition (Kutka & Richards, 1996;Hill et al, 2000;Hlúbiková et al, 2014) and can furtherly lead to a decrease in species richness (Bona et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The losses will include local, regional or global extinctions of species that prefer cold-water environments and cannot migrate beyond the northern coasts to escape warming and competition with warm-adapted species. In addition, as many Arctic freshwater species have specific adaptations to withstand freezing conditions during the winter, such cold-adapted species may be particularly threatened by ongoing climate warming (Tolonen et al, 2019). Hence, cold-adapted species can be considered as 'climate change losers', resulting in an irreversible loss of unique Arctic biodiversity.…”
Section: Winner S and Los Er S In The Face Of Climate Warmingmentioning
confidence: 99%